Molecular identification of a further branched-chain aminotransferase 7 (BCAT7) in tomato plant - Araújo, Wagner Luiz; Kochevenko, Andrej S.; Klee, Harry J.; Fernie, Alisdair R. (Journal of Plant Physiology, 2012)
Although the branched-chain amino acids (BCAAs) are essential components of the mammalian diet, our current understanding of their metabolism in plants is still limited. It is however well known that the branched-chain amino acid transaminases (BCATs) play a crucial role in both the synthesis and degradation of the BCAAs leucine, isoleucine and valine. We previously characterized the BCAT gene family in tomato, revealing it to be highly diverse in subcellular localization, substrate preference, and expression. Here we performed further characterization of this family and provide evidence for the presence of another member, BCAT7. On mapping the chromosomal location of this enzyme, it was possible to define the exact chromosome map position of the gene. Although in Arabidopsis thaliana the AtBCAT7 has been considered a pseudo-gene, quantitative evaluation of the expression levels of this gene revealed that the expression profile of the BCAT7 in different tissues of tomato (Solanum lycopersicum cv. M82) plants is highly variable with the highest expression found in developed flowers. By using a C-terminal E-GFP gene fusion we demonstrate that the BCAT7 is extraplastidial and in combination with the kinetic characterization of BCAT7 our results suggest that it most likely operates in BCAA degradation in vivo and support our hypothesis of another functional member of BCAT family. The combined data presented are discussed within the context of BCAA metabolism and its functions in higher plants.
Keywords: Branched-chain amino acids; Branched-chain amino acid transferase; Tomato; BCAT7; QTL